THE STUDENTS’ LEARNING STRATEGY AND MOTIVATION IN DEVELOPING THEIR SPEAKING ABILITY AT SIXTH SEMESTER OF ENGLISH DEPARTMENT (IAIN PAREPARE) - Era Dahlan; Abd. Haris Sunubi; Ahdar Ahdar (Institut Agama Islam Negeri Parepare, 2019)
The aim of this research was to know the Students learning startegy and motivation in developing the students’ speakin gability at six thse mester of English department (IAIN Parepare).The researcher was applying at six thse mester of English department (IAIN Parepare) through had escriptive qualitati veresearch. This research were using three kinds of instruments. The first instrument wastest, where the purpose of this instrument was to know the student tabilityin speaking. The second was interview, the aim of this instrument was to know what strategy that the student use to develop their speaking. The last was question naire, where this instrument was to know the motivation of the student in order to develop their speaking. After analyzing the data from the question naire the research erfound that students in the high andlow category have the same strong motivation in developing their speaking. However, interms of using strategy, the students in high category use more variated strategies than thelow category. The students in high category mostly apply cognitive and metacognitive strategy while the students in low cataegory mostly used social strategy.